Incidence and Prognostic Significance of PD-L1 Expression in High-Grade Salivary Gland Carcinoma - Fang, Qigen; Wu, Yao; Du, Wei; Zhang, Xu; Chen, Defeng (Frontiers in Oncology, 2021)
Objective: PD-L1 is one of the predictors of immunotherapy efficacy. Our goal was to analyze its expression and prognostic significance in high-grade salivary gland carcinoma (SGC). Methods: PD-L1 expression was evaluated using paraffin-embedded specimens from patients with surgically treated high-grade SGC, and it was scored by the tumor proportion score (TPS), combined positive score (CPS), and immune cell (IC) score. Associations between clinicopathological variables, disease-free survival (DFS), overall survival (OS) and PD-L1 expression were assessed. Results: TPS≥1% occurred in 47 patients with an incidence of 43.1%, and it was significantly related to an advanced tumor stage. In patients with TPS<1%, TPS ranging from 1% to 20%, and TPS≥20%, the 5-year DFS rates were 36%, 26%, and 13%, respectively, and the difference was significant. In patients with TPS<1%, TPS ranging from 1% to 20%, and TPS≥20%, the 5-year OS rates were 49%, 24%, and 13%, respectively, and the difference was significant. CPS≥1 occurred in 87 patients with an incidence of 79.8%. IC scores of 0, 1, 2, and 3 were noted in 24 (22.0%), 37 (33.9%), 31 (28.4%), and 17 (15.6%) patients, respectively. Both CPS and IC scores had no impact on DFS or OS. Conclusions: The expression of PD-L1 in tumor cells of high-grade SGCs was not uncommon, and it was significantly associated with tumor stage. PD-L1 expression in tumor cells rather than in immune cells indicated a poor prognosis.